The relationship between teacher candidates’ lifelong learning tendencies and their digital competencies - Keskin , Ismail (Asian Journal of Education and Training, 2023)
Digital competencies and lifelong learning tendencies are among the features that every teacher candidate should have. Therefore, carrying out research on both lifelong learning trends and digital competencies can contribute to the development and updating of teacher education programs. In this context, the aim of this research is to analyses the relationship between lifelong learning tendencies and digital competencies of teacher candidates. In this research, scanning model from descriptive research models and explanatory model from relational research methods were used. The sample of this research consists of 287 teacher candidates selected by simple random sampling method from among teacher candidates studying at this state university. In this study, two scales were used to determine the relationship between the lifelong learning tendencies of teacher candidates and their digital competencies. The first of these scales is the “Lifelong Learning Tendency Scale”. The second scale used in the research is the "Digital Competency Scale". There is a significant and moderate relationship between the lifelong learning tendencies scale in general and the competencies of using basic internet tools and the competencies of acquiring and using information in digital environment. Since there is a moderately significant relationship between lifelong learning tendencies and digital competence, these two concepts should be reflected in teacher education programs in a way that supports each other, without considering each other separately.